Extreme weather and civil war: Does drought fuel conflict in Somalia through livestock price shocks? - Maystadt, Jean-François; Ecker, Olivier (Wiley, 2014)
A growing body of evidence shows a causal relationship between extreme weather events and civil conflict incidence at the global level. We find that this causality is also valid for droughts and local violent conflicts in a within‐country setting over a short time frame in the case of Somalia. We estimate that a one standard deviation increase in drought intensity and length raises the likelihood of conflict by 62%. We also find that drought affects conflict through livestock price changes, establishing livestock markets as the primary channel of transmission in Somalia.